The Wisdom of The Prophetic Command in Requesting Science - Qahtan , Mohammed (Islamic Sciences Journal, 2023)
ABSTRACT Allah Almighty wanted the creatures to learn and contemplate issues of creation and the universe, so He sent prophets with laws and rulings. Therefore seeking knowledge was a basic goal of heavenly laws. After investigating the noble prophetic hadith I found what it had come in the form of the command to learn certain types of sciences, for the purpose of wisdom or a specific reason the Prophet (may God bless him and grant him peace) wanted to alert Muslims and encourage them to acqwire these sciences. I counted a number of noble hadiths that came in the form of the imperative, and asked Muslims to learn specific types of sciences, and my goal was to explain the prophetic wisdom in this matter by learning these specific sciences and not other sciences, and what impact later on, these sciences have on the Islamic community .